Elephant hunting patterns: the evidence of tusks in the ivory trade - Tom Pilgram; David Western (Pachyderm)
Reviews computer-simulated study intended to reflect the mortality of elephants due to hunting for ivory as compared with natural mortality, random culling and random hunting from mature and young populations.